1,25-Dihydroxyvitamin D inhibits hepatic diacyglycerol accumulation and ameliorates metabolic dysfunction in polycystic ovary syndrome rat models - Xin Yuan; Jianshu Yang; Danlin Sun; Danlin Sun; Kaiming Luo; Xiaohong Jiang; Long Wang; Shoukui Xiang; Yijie Jiang; Kele Ge; Zhiyang Zhou; Bowen Li; et al. (Frontiers Media S.A., 2023)
Introduction: We aimed to evaluate the influence of 1,25-dihydroxyvitamin D (1,25(OH)2D) on metabolic dysfunction and elucidate its underlying mechanism using a rat model of polycystic ovary syndrome (PCOS).Methods: Twenty-four Sprague-Dawley rats were randomly divided into four groups: control group (CON, 2 ml/kg of oral 0.5% CMC), 1,25VD group (oral 0.5% CMC and 2.5 ug/kg intraperitoneal 1,25(OH)2D), PCOS group (1 mg/kg oral letrozole), PCOS+1,25VD group (1 mg/kg oral letrozole orally 2.5 ug/kg intraperitoneal 1,25(OH)2D). The treatments were administered for 8 weeks. Body weight, estrus cycle, insulin tolerance, and oral glucose tolerance of the rats in the different groups were assessed. The rats were euthanized at the 8th weeks, and plasma, ovarian, and liver samples were collected and analyzed. The hepatic lipid profile was characterized using HPLC/MRM.Results: Letrozole-induced PCOS rats exhibited increased weight, insulin resistance, postprandial glucose abnormalities, and dyslipidemia. Compared with the PCOS group rats, the PCOS+1,25VD group rats showed reduced body weight, increased sensitivity to insulin, decreased postprandial glucose, and elevated levels of high-density lipoprotein cholesterol. Moreover, abnormally increased liver concentrations of total diacylglycerol (DG) and DG species in the PCOS rats were reversed by treatment with 1,25(OH)2D. Additionally, hepatic DG and insulin sensitivity were correlated.Conclusion: 1,25(OH)2D inhibited hepatic DG accumulation and ameliorated metabolic dysfunction in PCOS rat models.